Can an Increased Nitric Oxide Level be Accepted as Non-Invasive Marker for Sub/Acute Rejection of the Kidney Allograft?. Issue 12 (December 2013) - Masin-Spasovska, Jelka; Dohcev, Saso; Stankov, Oliver; Stavridis, Sotir; Saidi, Skender; Dejanova, Beti; Dejanov, Petar; Hristova-Dimceva, Anita; Dimitrovski, Koco; Spasovski, Goce
Background: Subclinical and acute rejections (SAR/AR) continue to have a negative impact on graft survival. The aim of our study was to analyze allograft rejection and nitric oxide (NO) levels in patients with protocol- and clinically-indicated biopsies in relationship with other causes of allograft dysfunction, and to evaluate the clinical impact of NO measurement as non-invasive marker for early diagnosis of SAR/AR. Methods: In 45 living-related kidney transplants, serum NO levels were measured at: 20 min after reperfusion (NO1); on days 1 (NO2), 5 (NO3), and 14 (NO4); and at the first (NO5) and sixth (NO6) months after transplantation (Tx). Protocol biopsies (Bx) were performed at the first and sixth months after Tx. Results: 38 (42.2%) Bx showed histological features of (SAR), 4 (4.5%) Bx showed mild tubulointerstitial rejection, while 48 (53.3%) Bx had no histological signs of SAR/AR. Significantly higher (NO3) levels were found in patients with AR and (NO5)/(NO6) in SAR as compared to other causes of allograft dysfunction occurred within the first posttransplant month (delayed graft function, urinary tract infection, and cyclosporine toxicity). Sensitivity/specificity for cut-off NO level of 70 μmol/l were 69.2% and 88.4% in AR, and 78.9% and 75.4% for the level of 50 μmol/l in SAR patients, respectively. Conclusions: Our study reports significantly higher serum NO levels at day 5 and a gradual decrease at day 14 (prior to and at the time of clinically manifested AR), and at 1- and 6-month protocol biopsies in SAR patients as compared to all other causes of renal dysfunction. NO measurement may have a satisfactorily diagnostic performance as a useful non-invasive marker not only for AR, but also for SAR patients.